Dumping socioambiental na organização mundial do comércio: a análise do baricentro do triângulo equilátero do desenvolvimento - Lau, Ana Isabella Bezerra (2017)
Based on a three-pillar development concept (social, environmental and economic), the paper aims to demonstrate, through the deductive hypothetical method, that there is no way to remove the WTO from certain controversies involving social and environmental rights, on the grounds that it is an exclusively commercial body. The practice of dumping, for example, to be perpetuated presupposes the reduction of production costs, which is most often done with the violation of social and environmental rights. In the first chapter, in constructing the concept of social and environmental dumping as a commercial practice punishable under the WTO Dispute Settlement Body, some difficulties are revealed. On the one hand, to outline the Organization's role in relation to socioenvironmental issues and, on the other hand, to recognize the existence of protectionism disguised as a humanitarian discourse, which is visible in attempts to impose social clauses as well as discriminatory trade barriers what is envisaged by the analysis of disputes brought to the institution's Dispute Settlement Body, which will be demonstrate in the second chapter. However, in spite of all the difficulties, it is imperative to recognize that the promotion of development (and not just economic growth, differentiation made in the third chapter) should be sought by the WTO when it is intended as a WTO objective. For this, the (external) transjuridicity is used to analyze the development from the perspective of the equilateral triangle, verifying how the position of the barycentre could be attributed to the multilateral organ, center of symmetry that supposedly could represent the balance between economic, social and environmental relations. In this scenario, and in view of the multiplicity of actors that appear in international trade, in the fourth chapter, legal pluralism (internal transjuridicity) is used, through the dialogue of sources and cooperation between these actors, inserting them in the litigation through the institute of amicus curiae. The purpose is build an effective performance of the WTO in the adjudication of complex cases, such as those of social and environmental dumping, and, with that, to keep alive the hope of promoting sustainable development.